Sacred suffering and the construction of political spirituality in the Iranian Shiism discourse - Jan, Zahra Khoshk (Critical research on religion, 2023)
This article tries to discuss this claim that Shia or as Henry Corbin puts it, “Iranian Islam,” is a discourse of political spirituality based on sacred suffering and governmentality (in Foucault's terms). The author aims to answer these questions: What do sacred suffering and governmentality mean in Shia discourse? How does sacred suffering articulate and give meaning to concepts related to political spirituality? To answer these questions, the author applied Laclau and Mouffe's discourse analysis, arguing that the sacred suffering constructs Shia antagonistic approach and plays a key role in constructing these discursive moments: the Karbala paradigm as a paradigm of both spirituality and political action, oppression, and martyrdom (as the holy death with spiritual-political goals). Moreover, in this discourse, the suffering of awaiting the Twelfth Imam during his absence becomes an opportunity to restore Shia governmentality through the establishment of a political government by Shia clerics in Iran.